Why can’t we see Allah? - Omer, Spahic (IIUM, 2019)
We cannot see Allah because, first, there is nothing like Him (al-Shura, 11). Our eyes, and other senses and faculties, are relative things and thus, can only see other relative things belonging to the corresponding existential realms. They cannot see, hear or recognize beyond the orb of our everyday existential things and objects. Second, nobody says that humans will not see Allah. Both the Holy Qur’an and the Prophet’s sunnah are explicit that believers will see Him in Paradise (jannah). The vision will be as clear and certain as seeing “the moon on the night when it is full” and “the sun on a cloudless day” (Sahih al-Bukhari). What is more, seeing Allah will be the best reward in Paradise; whereas not seeing Him will be the worst and most painful chastisement for the inhabitants of Hell. Seeing Allah is the greatest blessing and joy, so it is withheld for the place of ultimate blessing and joy, namely Paradise, and it is reserved exclusively for believers. This, in addition, serves to believers as a strong motive to continue doing good in this world and never get bored or give up. It goes without saying that not seeing Allah is only a temporary decree for Allah’s true servants, who are closest to Him in this world. Seeing Allah in Paradise could also imply the pinnacle, or culmination, of their incessant drawing closer to Him. Third, we cannot see Allah now and here because we are trapped in time and space, while He is beyond them. Time and space are Allah’s creation. He is not fettered by them; we are. Consequently, man cannot think except along the lines of time, space and matter. Once the hindrances posed by the time and space factors of this world are eliminated in the Hereafter -- or modulated, together with man himself and his various faculties, so as to make them suitable and fitting for the conditions of the Hereafter – seeing Allah will appear utterly viable and sensible, especially for those who will be Paradise-bound.